Prevention of child malocclusion: Pencegahan maloklusi pada anak - Siti Rachmatiara Dwi Destiarini; Sherly Horax; Marhamah; Fajriani; Eka Erwansyah (Makassar Dental Journal, 2023)
Malocclusion is a change in the normal relationship between the skeletal structure, muscles and teeth which can cause functional impairment and changes in the esthetics of the stomatognathic system. Malocclusion is the third most important oral health problem after caries and periodontal disease. The process of malocclusion can occur from early childhood with a prevalence reaching 89.9%. Malocclusion is very prone to occur in the mixed dentition period. This article aims to discuss about the pre-vention of malocclusion that occurs in children.